Crab & snail. The evil eel - Ferry, Beth (Ferry, Beth. Crab & Snail, 2023)
"The Evil Eel is so evil that one of her favorite hobbies is making narwhals cry. So evil in fact that just one sting turns friendly, sweet Snail into Snevil. Complete with a dark cape, Snevil sets out to destroy everything in her path, including Crab. In order to save himself--and his best friend--Crab must become a hero. Will he be able to stop evil from destroying the surf zone before it's too late?''--